The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Volume 3: Controls, Diagnostics and Instrumentation; Education; Electric Power; Microturbines and Small Turbomachinery; Solar B 2011
DOI: 10.1115/gt2011-45822
|View full text |Cite
|
Sign up to set email alerts
|

Geometry Optimization of Textured 3-D Micro-Thrust Bearings

Abstract: The paper presents an optimization study of the geometry of three-dimensional micro-thrust bearings, in a wide range of convergence ratios. The optimization goal is the maximization of the bearing load carrying capacity. The bearings are modeled as microchannels, consisting of a smooth moving wall (rotor), and a stationary wall (stator) with partial periodic rectangular texturing. The flow field is calculated from the numerical solution of the Navier-Stokes equations for incompressible isothermal flow; process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The best performance, in terms of load-carrying capacity, is obtained with a high density of texture, the textured area extending from 50% to 60% of relative length of the pad. [1][2][3][4] A fully textured pad does not, however, present any interest in terms of loadcarrying capacity. The cavity depth is also an important parameter and depends mainly on minimal film thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best performance, in terms of load-carrying capacity, is obtained with a high density of texture, the textured area extending from 50% to 60% of relative length of the pad. [1][2][3][4] A fully textured pad does not, however, present any interest in terms of loadcarrying capacity. The cavity depth is also an important parameter and depends mainly on minimal film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The present experimental investigation uses the optimal geometric parameters determined by Dobrica et al 4 Most of numerical studies have been isothermal. Recently, Papadopoulos et al 3 modeled a partially textured pad with square dimples and performed computational fluid dynamics simulations by taking into account local thermal effects. They showed that the load-carrying capacity decreases when thermal effects are integrated.…”
Section: Introductionmentioning
confidence: 99%
“…Sinanoglu et al 14 carried out an experiment of a dimpled shaft, which showed that appropriately dimpled journal shaft can improve the bearing's performances. In 2010, Papadopoulo et al 15 presented a method for optimizing the geometry size of three-dimensional (3D) micro-thrust bearings in a wide range of convergence ratios. In 2011, Qiu and Khonsari 16 studied the cavitation pressure effect on tribological performance of mechanical seal-like thrust bearings with dimples by solving the Reynolds equation with a mass conservative algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid density [16] used CFD code to analyze the effects of the rolling speed, oil viscosity, and supplying oil concentration on the pressure distributions of oil and water phases. Zhang et al [17], Brajdic-Mitidieri et al [18] and Papadopoulos et al [19] optimized the geometry of inclined thrust bearings, pocketed pad bearings and textured micro-thrust bearings using CFD techniques respectively. CFD widens the range of solvable lubrication problems and makes design process more convenient.…”
mentioning
confidence: 99%